Apelin-13 Attenuates Lipopolysaccharide-Induced Inflammatory Responses and Acute Lung Injury by Regulating PFKFB3-Driven Glycolysis Induced by NOX4-Dependent ROS - Yuan Y; Wang W; Zhang Y; Hong Q; Huang W; Li L; Xie Z; Chen Y; Li X; Meng Y (Dove Medical Press, 2022)
Yafei Yuan,1 Wei Wang,1 Yue Zhang,1 Qiaohui Hong,1 Wenhui Huang,1 Lijuan Li,1 Zhanzhan Xie,1 Yixin Chen,1 Xu Li,2,3 Ying Meng1 1Department of Respiratory and Critical Care Medicine, Nanfang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 2Department of Emergency Medicine, Nanfang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 3Ministry of Education, Key Laboratory of Hainan Trauma and Disaster Rescue, College of Emergency and Trauma, Hainan Medical University, Haikou, 571199, People's Republic of ChinaCorrespondence: Ying Meng, Department of Respiratory and Critical Care Medicine, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People's Republic of China, Tel/Fax +86 20-62787112, Email nfyymengy@163.com Xu Li, Department of Emergency Medicine, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People's Republic of China, Email mylx99@163.comPurpose: Acute lung injury (ALI) is a life-threatening condition with limited therapeutic options. Macrophage inflammation plays a key role in the development of ALI. Abnormal glycolysis of macrophages contributes to the inflammatory response. However, the role of macrophage glycolysis in ALI still requires investigation. Apelin-13 has been shown to protect against ALI, whereas the underlying mechanisms remain unclear. In this study, we explored the effect of apelin-13 on lipopolysaccharide (LPS)-induced inflammation and ALI via regulation of glycolysis by modulating redox homeostasis in macrophages.Methods: Serums from 34 patients with sepsis and 13 healthy volunteers were analyzed. In vivo, the protective effect of apelin-13 against LPS-induced ALI was evaluated using a mouse model of LPS-induced ALI. In vitro, mouse bone marrow macrophages (BMDMs) were pretreated with the antioxidant, NADPH oxidase (NOX) 4 (NOX4) small-interfering RNA (siRNA), the 6-phosphofructo-2 -kinase/fructose- 2,6-biphosphatase 3 (PFKFB3) siRNA, or the PFKFB3 overexpression plasmid before exposure to LPS.Results: Serum apelin-13 levels were significantly elevated in patients with sepsis and sepsis-associated acute respiratory distress syndrome (ARDS) (P< 0.0001). In vivo, apelin-13 suppressed LPS-induced ALI and inflammatory cytokine production (P< 0.05). Furthermore, apelin-13 reduced hydrogen peroxide (H2O2) content, NOX4 protein levels, and glycolysis. In vitro, LPS stimulation elevated NOX4 protein levels and reactive oxygen species (ROS) production (P< 0.05). These changes resulted in the accumulation of glycolysis in BMDMs. Treatment with antioxidant or NOX4 siRNA inhibited LPS-induced glycolysis and inflammatory cytokine production (P< 0.05). Moreover, in vitro experiments revealed that PFKFB3 regulates the release of pro-inflammatory cytokines by modulating glycolysis. In contrast, the action of apelin-13 opposed the effects of LPS.Conclusion: In conclusion, apelin-13 protects against LPS-induced inflammatory responses and ALI by regulating PFKFB3-driven glycolysis induced by NOX4-dependent ROS.Keywords: acute lung injury, inflammation, mice, apelin-13, NADPH oxidase 4, glycolysis, PFKFB3